ESTIMATIVA DE CONSUMO PARA RECUPERAÇÃO DE PERDAS NÃO-TÉCNICAS DE ENERGIA ELÉTRICA METODOLOGIA PARA DETERMINAÇÃO DE FATORES DE CARGA E DE DEMANDA TÍPICOS DE ATIVIDADES COMERCIAIS - Flor, Ricardo Antonio Maciel (2010)
This dissertation presents a research methodology for estimating the energy consumption of commercial consumer units of COELBA, for recovery of nontechnical energy loss by determination of typical load factors and demand factors of similar consumers. The results expect to improve consumer relations between company and consumer of electricity. The development of methodology has statistical basement. For sizing of samples of research, aspects such as geographical area, classes and tracks consumption were considered, resulting in the determination of load factors and demand factors. The research results in estimates of consumption closer to reality, if compared to the values obtained by current estimates. This dissertation was motivated by ANEEL R&D project, cycle 2006-2007, no. 0047-006/2007 entitled Definição de Fatores de Carga e de Demanda Típicos de Unidades Consumidoras Comerciais de Baixa Tensão da Região Metropolitana de Salvador , which the author was manager and developed along with researchers Monica Silveira and Roberto Pedro Paiva Dantas.